2010
DOI: 10.17323/1609-4514-2010-10-3-485-517
|View full text |Cite
|
Sign up to set email alerts
|

Moments of Quadratic Dirichlet L-Functions over Rational Function Fields

Abstract: We establish the meromorphic continuation of a multiple Dirichlet series associated to the fourth moment of quadratic Dirichlet L-functions, over the rational function field Fq(T) with q odd, up to its natural boundary. This is the first such result in which the group of functional equations is infinite; in such cases, it is expected that the series cannot be continued everywhere but can at least be extended to a large enough region to deduce asymptotics at the central point. In this case, these asymptotics co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…As with Theorem 1.1 for simplicity we have restricted attention to fundamental discriminants of the form 8d, and we may adapt our methods to cover other discriminants. In families of discriminants where the sign of the functional equation is negative, we may adapt our methods to study the second moment of the derivative of the L-function at 1 2 . Further, we may adapt the technique described here to obtain an asymptotic formula for the fourth moment of quadratic Dirichlet L-functions, conditional on the GRH.…”
Section: Introductionmentioning
confidence: 99%
“…As with Theorem 1.1 for simplicity we have restricted attention to fundamental discriminants of the form 8d, and we may adapt our methods to cover other discriminants. In families of discriminants where the sign of the functional equation is negative, we may adapt our methods to study the second moment of the derivative of the L-function at 1 2 . Further, we may adapt the technique described here to obtain an asymptotic formula for the fourth moment of quadratic Dirichlet L-functions, conditional on the GRH.…”
Section: Introductionmentioning
confidence: 99%
“…As q → ∞, they showed that the Frobenii classes become equidistributed in the group USp(2g), so computing the moment reduces to computing a matrix integral over USp(2g), which was done by Keating and Snaith [20]. Note that in the q → ∞ regime, Bucur and Diaconu [3] obtained an asymptotic formula for D monic deg(D)=2g L(1/2, χ D ) 4 , using multiple Dirichlet series. Hence we concentrate on the limit g → ∞ (with q fixed), which is more similar to the original number field problem.…”
mentioning
confidence: 99%
“…we conclude that φ(g) is bounded by the product of a −α , the sup norms δ(X)φ ∞ for any X in (A. 7), and a constant that depends only on S t . Theorem A.3.1 then follows from iterating this procedure for various simple roots α and applying the estimate in proposition A.2.5.…”
Section: 8mentioning
confidence: 73%
“…We note that the (presently missing) integration theory could also yield meromorphic continuations of non-constant Fourier-Whittaker coefficients. If applied to Eisenstein series on covers of loop groups, this could potentially be a source of new meromorphic continuations of multiple Dirichlet series, such as ones used for studying moments of Dirichlet L-functions (see [7], which has a detailed discussion of the fourth moment problem for quadratic characters.). be the sets of positive and negative roots, respectively.…”
Section: 3mentioning
confidence: 99%